Evolution of syncarpy and other morphological characters in African Annonaceae: A posterior mapping approach (2008)
The congenital fusion of carpels, or syncarpy, is considered a key innovation as it is found in more than 80% of angiosperms. Within the magnoliids however, syncarpy has rarely evolved. Two alternative evolutionary origins of syncarpy were suggested in order to explain the evolution of this feature: multiplication of a single carpel vs. fusion of a moderate number of carpels. The magnoliid family Annonaceae provides an ideal situation to test these hypotheses as two African genera, Isolona and Monodora, are syncarpous in an otherwise apocarpous family with multicarpellate and unicarpellate genera. In addition to syncarpy, the evolution of six other morphological characters was studied. Well-supported phylogenetic relationships of African Annonaceae and in particular those of Isolona and Monodora were reconstructed. Six plastid regions were sequenced and analyzed using maximum parsimony and Bayesian inference methods. The Bayesian posterior mapping approach to study character evolution was used as it accounts for both mapping and phylogenetic uncertainty, and also allows multiple state changes along the branches. Our phylogenetic analyses recovered a fully resolved clade comprising twelve genera endemic to Africa, including Isolona and Monodora, which was nested within the so-called long-branch clade. This is the largest and most species-rich clade of African genera identified to date within Annonaceae. The two syncarpous genera were inferred with maximum support to be sister to a clade characterized by genera with multicarpellate apocarpous gynoecia, supporting the hypothesis that syncarpy arose by fusion of a moderate number of carpels. This hypothesis was also favoured when studying the floral anatomy of both genera. Annonaceae provide the only case of a clear evolution of syncarpy within an otherwise apocarpous magnoliid family. The results presented here offer a better understanding of the evolution of syncarpy in Annonaceae and within angiosperms in general.